LEGAL INSTRUMENTS OF COMBATING LEGALIZATION (LAUNDERING) OF PROCEEDS OF CRIME IN CONDITIONS OF DIGITAL EVOLUTION OF THE REPUBLIC OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2024)
The article investigates domestic legal instruments used in combating legalization (laundering) of proceeds of crime in the conditions of digital criminal development. The purpose of this article is to introduce the results of the authors' research area to the scientific community. Legalization (laundering) of proceeds of crime poses a serious threat to the financial stability and economic security of the state as a whole. One of the factors having a negative impact on the traditional financial system has become the spread of digital assets, including cryptocurrencies, NFT - tokens, the volume of transactions has an annual exponential growth. The main principle of legalization of criminal proceeds assumes complete disclosure of criminal activities from law enforcement and controlling authorities and their further involvement in legitimate economic activities, as blockchain technologies allow to perform these activities anonymously. Measures taken by state authorities to prevent criminal legalization (laundering) of money and proceeds, such as regulations, financial transaction monitoring systems, international cooperation and measures to strengthen financial transparency are analyzed. The development, adoption and implementation of a comprehensive system of measures aimed at protecting the rights and legitimate interests of citizens and society, the state and the organization of the legal mechanism in combating money laundering requires the adoption and consistent implementation of effective measures.The significance of the performed research resides in the possibility of application of the obtained results in the field of combating criminal legalization (laundering) of proceeds. In the course of the research, the article highlights the issues of efficiency and possible upgrading of legal instruments in the context of combating criminal legalization (laundering) of proceeds in Kazakhstan. Emphasis is placed on the efficiency of these instruments and possible implementation difficulties.Keywords: legalization, laundering of the criminal income, combatting, digital assets, cryptocurrencies.